Organizing Foreign Language Lessons in Primary Education - Jumaniyozova Sevinchoy Farxod qizi (Genius Journals, 2023)
In this article, the task and skills of pedagogues to improve foreign language skills in elementary school students, how important foreign language is for students, the correct organization of foreign language classes, different types of foreign language classes the use of methods is discussed.
Keywords: teacher; foreign language; English language; school